One-step preparation method of nitrogen self-doped activated carbon, product and application
The nitrogen self-doped activated carbon was prepared by a one-step method, and activated carbon was synthesized under the cover of molten salt by using a mixture of melamine and terephthalaldehyde and potassium hydroxide. This solved the problems of complex preparation and high energy consumption of existing activated carbons, and achieved high performance and low cost activated carbon production.
Patent Information
- Application Number
- CN202510694666.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-08-29
AI Technical Summary
The existing activated carbon preparation process is complex, requiring inert gas protection, high energy consumption, single pores, complex post-treatment, and difficult industrialization.
Melamine and terephthaldehyde are mixed with potassium hydroxide, and molten salt is used to cover and isolate the air to achieve synthesis, carbonization and activation to complete the preparation of activated carbon to avoid protection of inert gas.
The prepared nitrogen self-doped activated carbon has a high specific surface area and a rich pore structure, excellent electrochemical performance, and reduces production costs.
Smart Images

Figure CN120565307A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of activated carbon materials, and in particular to a one-step preparation method, product and application of nitrogen self-doped activated carbon. Background Art
[0002] The development of supercapacitors in the renewable energy sector has attracted much attention, and activated carbon electrode materials have become a key factor. The electric double-layer capacitor (EDLC) in supercapacitors relies on electrostatic adsorption to store charge, and has high power density and cycle stability. Its performance is closely related to the specific surface area of the electrode material. Activated carbon stands out due to its unique advantages. It has a rich pore structure and can provide a large specific surface area, which provides ample space for charge storage and greatly improves the energy storage capacity of supercapacitors. At the same time, activated carbon is widely available and relatively low in cost, which makes it highly competitive in the application of supercapacitor electrode materials, and strongly promotes the development and application of supercapacitors in the field of energy storage.
[0003] However, the activated carbon preparation process currently used on the market is complex and requires inert gas protection; these activated carbon preparation methods have high energy consumption, single pores, complex post-processing, high equipment costs, and difficulty in industrialization. Summary of the Invention
[0004] Based on the above, the present invention provides a one-step preparation method, product, and application of nitrogen-doped activated carbon. By selecting nitrogen-containing materials (melamine and terephthalaldehyde), adding potassium hydroxide for activation, and then shielding the activated carbon with molten salt to isolate it from air, the method achieves a one-step synthesis, carbonization, and activation process, without the need for inert gas protection.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a one-step preparation method of nitrogen self-doped activated carbon, comprising the following steps:
[0007] After mixing melamine and terephthalaldehyde, the mixture is mixed with potassium hydroxide solution to obtain a paste-like mixture;
[0008] Evaporating the water in the paste mixture to obtain mixture A;
[0009] Covering the surface of the mixture A with salt and then carbonizing it to obtain a crude product;
[0010] The crude product is soaked in dilute hydrochloric acid to obtain the nitrogen self-doped activated carbon (abbreviated as: activated carbon).
[0011] The second technical solution of the present invention is a nitrogen self-doped activated carbon prepared according to the above preparation method.
[0012] The third technical solution of the present invention is a double-layer supercapacitor, comprising a negative electrode shell, an activated carbon electrode, a PP diaphragm, a positive electrode shell and an electrolyte; the activated carbon electrode is made of the above-mentioned nitrogen self-doped activated carbon.
[0013] The present invention discloses the following technical effects:
[0014] This invention uses melamine and terephthalaldehyde as the main raw materials and potassium hydroxide as the activator. A "dissolve-mix-evaporate" method is used to uniformly mix flaky potassium hydroxide with solid powders of melamine and terephthalaldehyde. A molten salt system of sodium chloride and calcium chloride is employed to produce activated carbon without the protection of an inert gas.
[0015] The BET specific surface area of the activated carbon prepared by the method of the present invention reaches 747.73m 2 / g, with an average pore size of 3.01nm. The activated carbon was prepared into an activated carbon electrode for electrochemical testing, and the specific capacitance reached 177.9F / g at 0.1A / g. The activated carbon preparation method of the present invention is simple and efficient, reduces production costs, and the prepared activated carbon has excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 The cyclic voltammetry (CV) curve of the activated carbon prepared in Example 1 was obtained at a scan rate of 10 mV / s.
[0018] Figure 2 The charge and discharge CP curve of the activated carbon prepared in Example 1 at a current density of 0.1 A / g.
[0019] Figure 3 The specific capacitance change curve of the activated carbon prepared in Example 1 at different current densities.
[0020] Figure 4 The cyclic voltammetry (CV) curve of the activated carbon prepared in Example 2 was obtained at a scan rate of 10 mV / s.
[0021] Figure 5 This is the charge and discharge CP curve of the activated carbon prepared in Example 2 at a current density of 0.1 A / g.
[0022] Figure 6The specific capacitance change curve of the activated carbon prepared in Example 2 at different current densities.
[0023] Figure 7 The cyclic voltammetry (CV) curve of the activated carbon prepared in Example 3 was obtained at a scan rate of 10 mV / s.
[0024] Figure 8 This is the charge and discharge CP curve of the activated carbon prepared in Example 3 at a current density of 0.1 A / g.
[0025] Figure 9 The specific capacitance change curve of the activated carbon prepared in Example 3 at different current densities. DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] The first aspect of the present invention provides a one-step preparation method of nitrogen self-doped activated carbon, comprising the following steps:
[0032] After mixing melamine and terephthalaldehyde, the mixture is mixed with potassium hydroxide solution to obtain a paste-like mixture;
[0033] Evaporating the water in the paste mixture to obtain mixture A;
[0034] Covering the surface of the mixture A with salt and then carbonizing it to obtain a crude product;
[0035] The crude product is soaked in dilute hydrochloric acid to obtain the nitrogen self-doped activated carbon (abbreviated as: activated carbon).
[0036] The invention adopts the operation of first dissolving potassium hydroxide, mixing the potassium hydroxide with raw materials into a paste and then drying the mixture, thereby solving the problem that potassium hydroxide solid is difficult to grind uniformly.
[0037] The present invention adopts a molten salt method to sinter the raw materials. This method can not only etch the activated carbon to form a rich pore structure, but also isolate the air, so that the activated carbon can be prepared without the protection of inert gas.
[0038] In a preferred embodiment of the present invention, the molar ratio of the melamine to the terephthalaldehyde is 2:3.
[0039] In a preferred embodiment of the present invention, the mass of potassium hydroxide in the potassium hydroxide solution is 0.5 to 2.0 times the sum of the masses of melamine and terephthalaldehyde.
[0040] In the present invention, if the amount of potassium hydroxide used is too small, the etching and activation effect on the carbon is insufficient, resulting in low porosity of the activated carbon. If the amount of potassium hydroxide used is too large, the etching effect on the carbon is too strong, which will cause pore collapse and destroy the pore structure. Therefore, the present invention preferably limits the mass of potassium hydroxide to 0.5 to 2.0 times the sum of the masses of melamine and terephthalaldehyde.
[0041] The present invention does not impose any particular limitation on the concentration of the potassium hydroxide solution. The solvent of the potassium hydroxide solution is water. The amount of the solvent used can be such that melamine, terephthalaldehyde and potassium hydroxide are mixed into a paste.
[0042] In a preferred embodiment of the present invention, the evaporation temperature is 130° C. and the time is 1 hour.
[0043] In a preferred embodiment of the present invention, the salt is a mixture of sodium chloride and calcium chloride in a mass ratio of 1:3.
[0044] In a preferred embodiment of the present invention, the thickness of the salt covering the surface of the mixture A is 3 mm.
[0045] In a preferred embodiment of the present invention, the carbonization is specifically performed by heating the temperature to 700-800° C. at a rate of 3° C. / min and then maintaining the temperature for 2 hours.
[0046] In the present invention, if the carbonization temperature is too low, it will not reach the eutectic point of the molten salt and will not be able to isolate the air. If the temperature is too high, it will lead to excessive decomposition and a low yield of activated carbon. In addition, high temperature will cause the micropore and mesopore structure of the carbon to collapse and the porosity to decrease. Therefore, the present invention preferably limits the carbonization temperature to between 700 and 800°C.
[0047] In a preferred embodiment of the present invention, the concentration of the dilute hydrochloric acid is 1 mol / L, and the soaking time in the dilute hydrochloric acid is 30 minutes. Ultrasonic treatment is also performed during the soaking process; the present invention does not impose any particular limitation on the power of the ultrasonic treatment, and the ultrasonic treatment power commonly used by those skilled in the art can be used.
[0048] In a preferred embodiment of the present invention, the mass of 1 mol / L dilute hydrochloric acid is at least 20 times the mass of potassium hydroxide solid.
[0049] After soaking the crude product with dilute hydrochloric acid, the method further comprises the steps of washing, filtering and drying the soaked product.
[0050] The melamine used in this invention contains nitrogen, which enhances the electron mobility of the activated carbon and improves its catalytic performance in electron transfer reactions. The reaction between melamine and terephthalaldehyde forms a large, cyclic macromolecular structure, which provides the activated carbon with a rich pore structure, increasing its specific surface area and thus its specific capacitance.
[0051] Potassium hydroxide, as an activator, can etch activated carbon at high temperatures, creating a rich porous structure. However, potassium hydroxide is generally flaky and not easily grinded and mixed directly with melamine and terephthalaldehyde powders. Therefore, it is first dissolved in deionized water and evenly mixed with the raw materials (melamine and terephthalaldehyde) to form a paste. The water is then dried in a muffle furnace at 130°C for 1 hour. This produces a uniformly mixed solid mixture of melamine, terephthalaldehyde, and potassium hydroxide, achieving sufficient contact between the solids and facilitating subsequent coverage with the mixed salt.
[0052] When sodium chloride and calcium chloride are thoroughly mixed in a 1:3 ratio, a eutectic point is reached at around 500°C. The mixed salt melts into a liquid coating, isolating the upper layer from the outside air and achieving the desired activated carbon production without the introduction of an inert gas. The mixed salt needs to be laid to a thickness of 3mm. Too little mixed salt will result in poor air isolation, while too much will lead to uneven heating of the material during firing and make the activated carbon difficult to wash.
[0053] The activated carbon firing process adopts a slow heating method at 3°C / min to uniformly heat the materials in the ceramic crucible, so that the synthesis of melamine and terephthalaldehyde in the crucible, melting of mixed salts, and formation of activated carbon are carried out slowly and step by step.
[0054] The purpose of soaking the product in dilute hydrochloric acid is to cause an oxidation-reduction reaction with the residual activator potassium hydroxide to fully remove potassium hydroxide impurities in the product.
[0055] A second aspect of the present invention provides nitrogen self-doped activated carbon prepared according to the above preparation method.
[0056] The third aspect of the present invention provides a double-layer supercapacitor, comprising a negative electrode shell, an activated carbon electrode, a PP separator, a positive electrode shell and an electrolyte; the activated carbon electrode is made of the above-mentioned nitrogen self-doped activated carbon.
[0057] Unless otherwise specified, the technical solutions described in the present invention are all conventional solutions in the field, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0058] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0059] Example 1
[0060] Weigh 1.26g of melamine and 2.01g of terephthalaldehyde, place them in a ceramic mortar and grind them thoroughly, and add the mixture to a ceramic crucible. Weigh 1.635g of potassium hydroxide (0.5 times the total mass of melamine and terephthalaldehyde) and place it in a beaker. Add 5mL of deionized water and stir thoroughly with a glass rod to completely dissolve the potassium hydroxide. Pour it into a ceramic crucible containing a mixture of melamine and terephthalaldehyde, stir it thoroughly with a glass rod to form a paste, and make its surface as smooth as possible to facilitate subsequent coverage with molten salt. Place the ceramic crucible in a muffle furnace, heat it to 130°C at 5°C / min, and keep it at this temperature for 1h. Evaporate the water in the ceramic crucible.
[0061] Weigh 3g of sodium chloride and 9g of calcium chloride into a ceramic crucible. After thoroughly grinding and mixing, evenly coat the evaporated mixture of melamine, terephthalaldehyde, and potassium hydroxide to a thickness of 3mm. Place the mixture in a muffle furnace, cover it, and heat at 3°C / min to 700°C. Hold the temperature for 2 hours, then remove the crucible after cooling to room temperature.
[0062] 150 mL of 1 mol / L dilute hydrochloric acid was added to a ceramic crucible and stirred continuously for a full reaction. The mixture was then ultrasonicated for 30 minutes. The mixture was washed five times with deionized water, filtered, and dried in an oven at 60°C overnight to obtain activated carbon.
[0063] The activated carbon prepared in this example was subjected to BET surface area test, and its BET specific surface area reached 747.73 m 3 / g, with a total pore volume of 0.56 cm 3 / g, with an average pore size of 3.01nm. The high specific surface area and pore size distribution concentrated in the micropore and mesopore range indicate that the activated carbon has a rich pore structure.
[0064] According to a typical electrode preparation process, the activated carbon, acetylene black, and PTFE prepared in this example were dispersed in anhydrous ethanol at a mass ratio of 8:1.5:0.5. After stirring for 3 hours, the mixture was dried in an oven for 12 hours. The dried mixture was mixed with a small amount of ethanol to form a paste, which was then pressed using a roller press to form a paste with an area of approximately 1 cm. 2 The porous carbon sheet was then dried at 80 °C for 12 h. The porous carbon sheet was then pressed onto a stainless steel mesh (1.5 × 1.5 cm) using a roller press. 2 ) to obtain an activated carbon electrode. The activated carbon electrodes prepared in this example were assembled into a symmetrical double-layer supercapacitor (double-layer supercapacitor structure: negative electrode shell-activated carbon electrode-PP diaphragm-activated carbon electrode-positive electrode shell, the electrolyte was 1M sulfuric acid solution; the electrochemical performance of the activated carbon product prepared in Example 1 was tested using a chi660e electrochemical workstation, and the cyclic voltammetry CV curve at a scan rate of 10mV / s was as shown below. Figure 1 As shown. Figure 1 It can be seen that the activated carbon prepared in Example 1 has a nearly rectangular shape and exhibits good double-layer capacitance characteristics. Figure 2 CP curve of the activated carbon prepared in Example 1 at a current density of 0.1 A / g. It can be seen that the charge and discharge image of the activated carbon prepared in Example 1 presents an approximately isosceles triangle, showing good reversibility. Figure 3 The specific capacitance change curve of the activated carbon prepared in Example 1 under different current densities; the specific capacitance at 0.1 A / g reaches a high specific capacitance of 177.9 F / g, and the specific capacitance at 1.0 A / g can still reach a specific capacitance of 155.9 F / g, maintaining 87.6% of its initial capacitance, and has good electrochemical properties.
[0065] Example 2
[0066] Weigh 1.26g of melamine and 2.01g of terephthalaldehyde, place them in a ceramic mortar and grind them thoroughly, and add the mixture to a ceramic crucible. Weigh 3.27g of potassium hydroxide (1.0 times the total mass of melamine and terephthalaldehyde) and place it in a beaker. Add 5mL of deionized water and stir thoroughly with a glass rod to completely dissolve the potassium hydroxide. Pour it into a ceramic crucible containing the mixture of melamine and terephthalaldehyde, stir it thoroughly with a glass rod to form a paste, and make its surface as smooth as possible to facilitate subsequent coverage with molten salt. Place the ceramic crucible in a muffle furnace, heat it to 130°C at 5°C / min, and keep it at a constant temperature for 1h. Evaporate the water in the ceramic crucible.
[0067] Weigh 3g of sodium chloride and 9g of calcium chloride into a ceramic crucible. After thoroughly grinding and mixing, evenly coat the evaporated mixture of melamine, terephthalaldehyde, and potassium hydroxide to a thickness of 3mm. Place the mixture in a muffle furnace, cover it, and heat at 3°C / min to 700°C. Hold the temperature for 2 hours, then remove the crucible after cooling to room temperature.
[0068] Add 150 mL of 1 mol / L dilute hydrochloric acid to a ceramic crucible and stir continuously to allow for full reaction. Ultrasonicate for 30 minutes. Wash with deionized water five times, filter, and dry in a 60°C oven overnight.
[0069] The activated carbon prepared in this example was subjected to BET surface area test, and its BET specific surface area reached 702.56 m 3 / g, with a total pore volume of 0.43 cm 3 / g, with an average pore size of 3.52nm. The high specific surface area and pore size distribution concentrated in the micropore and mesopore ranges indicate that the activated carbon has a rich pore structure, and activated carbon is obtained (i.e., the only difference from Example 1 is that the amount of potassium hydroxide added is 3.27g; the other steps and parameters are the same as Example 1).
[0070] The activated carbon prepared in this example was dispersed in anhydrous ethanol with acetylene black and PTFE in a mass ratio of 8:1.5:0.5. After stirring for 3 hours, the mixture was dried in an oven for 12 hours. The dried mixture was mixed with a small amount of ethanol to form a paste, which was then pressed using a roller press to form a paste with an area of approximately 1 cm. 2 The porous carbon sheet was then dried at 80 °C for 12 h. The porous carbon sheet was then pressed onto a stainless steel mesh (1.5 × 1.5 cm) using a roller press. 2) to obtain an activated carbon electrode. The activated carbon electrodes prepared in this example were assembled into a symmetrical double-layer supercapacitor (capacitor structure: negative electrode shell-activated carbon electrode-pp diaphragm-activated carbon electrode-positive electrode shell, the electrolyte was 1M sulfuric acid solution). The electrochemical performance of the activated carbon product prepared in Example 1 was tested using a chi660e electrochemical workstation, and the cyclic voltammetry CV curve at a scan rate of 10mV / s was as shown below. Figure 4 As shown in . Figure 4 It can be seen that the activated carbon prepared in Example 2 has a nearly rectangular shape and exhibits good double-layer capacitance characteristics. Figure 5 CP curve of the activated carbon prepared in Example 2 at a current density of 0.1 A / g. It can be seen that the charge and discharge image of the activated carbon prepared in Example 2 presents an approximately isosceles triangle, showing good reversibility. Figure 6 The specific capacitance change curve of the activated carbon prepared in Example 2 under different current densities; the specific capacitance at 0.1 A / g reaches a high specific capacitance of 171.3 F / g, and the specific capacitance at 1.0 A / g can still reach a specific capacitance of 147.7 F / g, maintaining 86.2% of its initial capacitance, and has good electrochemical properties.
[0071] Example 3
[0072] Weigh 1.26g of melamine and 2.01g of terephthalaldehyde, place them in a ceramic mortar and grind them thoroughly, and add the mixture to a ceramic crucible. Weigh 6.54g of potassium hydroxide (2.0 times the mass of melamine and terephthalaldehyde) and place it in a beaker. Add 5mL of deionized water and stir thoroughly with a glass rod to completely dissolve the potassium hydroxide. Pour it into a ceramic crucible containing a mixture of melamine and terephthalaldehyde, stir it thoroughly with a glass rod to form a paste, and make its surface as smooth as possible to facilitate subsequent coverage with molten salt. Place the ceramic crucible in a muffle furnace, heat it to 130°C at 5°C / min, and keep it at a constant temperature for 1h. Evaporate the water in the ceramic crucible.
[0073] Weigh 3g of sodium chloride and 9g of calcium chloride into a ceramic crucible. After thoroughly grinding and mixing, evenly coat the evaporated mixture of melamine, terephthalaldehyde, and potassium hydroxide to a thickness of 3mm. Place the mixture in a muffle furnace, cover it, and heat at 3°C / min to 800°C. Hold the temperature for 2 hours, then remove the crucible after cooling to room temperature.
[0074] 150 mL of 1 mol / L dilute hydrochloric acid was added to a ceramic crucible and stirred continuously for a full reaction. The mixture was then ultrasonicated for 30 minutes. The mixture was washed five times with deionized water, filtered, and dried in an oven at 60°C overnight to obtain activated carbon.
[0075] The activated carbon prepared in this example was subjected to BET surface area test, and its BET specific surface area reached 688.40 m 3 / g, with a total pore volume of 0.40 cm 3 / g, with an average pore size of 4.27nm. The high specific surface area and pore size distribution concentrated in the micropore and mesopore ranges indicate that the activated carbon has a rich pore structure.
[0076] According to a typical electrode preparation process, the activated carbon, acetylene black, and PTFE prepared in this example were dispersed in anhydrous ethanol at a mass ratio of 8:1.5:0.5. After stirring for 3 hours, the mixture was dried in an oven for 12 hours. The dried mixture was mixed with a small amount of ethanol to form a paste, which was then pressed using a roller press to form a paste with an area of approximately 1 cm. 2 The porous carbon sheet was then dried at 80 °C for 12 h. The porous carbon sheet was then pressed onto a stainless steel mesh (1.5 × 1.5 cm) using a roller press. 2 ) to obtain an activated carbon electrode. The activated carbon electrodes prepared in this example were assembled into a symmetrical double-layer supercapacitor (capacitor structure: negative electrode shell-activated carbon electrode-pp diaphragm-activated carbon electrode-positive electrode shell, the electrolyte was 1M sulfuric acid solution). The electrochemical performance of the activated carbon product prepared in Example 1 was tested using a chi660e electrochemical workstation, and the cyclic voltammetry CV curve at a scan rate of 10mV / s was as shown below. Figure 7 As shown in . Figure 7 It can be seen that the activated carbon prepared in Example 3 has a nearly rectangular shape and exhibits good double-layer capacitance characteristics. Figure 8 CP curve of the activated carbon prepared in Example 3 at a current density of 0.1 A / g. It can be seen that the charge and discharge image of the activated carbon prepared in Example 3 presents an approximately isosceles triangle, showing good reversibility. Figure 9 The specific capacitance curves of the activated carbon prepared in Example 3 at different current densities are shown. The specific capacitance at 0.1 A / g reaches 158.2 F / g, and at 1.0 A / g it still reaches 144.0 F / g, maintaining 91.0% of its initial capacitance, demonstrating excellent electrochemical performance.
[0077] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.
Claims
1. A one-step preparation method of nitrogen self-doped activated carbon, characterized in that: The following steps are involved: After mixing melamine and terephthalaldehyde, the mixture is mixed with potassium hydroxide solution to obtain a paste-like mixture; Evaporating the water in the paste mixture to obtain mixture A; Covering the surface of the mixture A with salt and then carbonizing it to obtain a crude product; The crude product is soaked in dilute hydrochloric acid to obtain the nitrogen self-doped activated carbon.
2. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The molar ratio of the melamine to the terephthalaldehyde is 2:
3.
3. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The mass of potassium hydroxide in the potassium hydroxide solution is 0.5 to 2.0 times the sum of the masses of melamine and terephthalaldehyde.
4. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The evaporation temperature is 130° C. and the time is 1 h.
5. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The salt is a mixture of sodium chloride and calcium chloride in a mass ratio of 1:
3.
6. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The thickness of the salt covering the surface of the mixture A is 3 mm.
7. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The carbonization step is to increase the temperature to 700-800° C. at a rate of 3° C. / min and then maintain the temperature for 2 hours.
8. The one-step preparation method of nitrogen self-doped activated carbon according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid is 1 mol / L; the soaking time in the dilute hydrochloric acid is 30 min.
9. Nitrogen self-doped activated carbon prepared by the preparation method according to any one of claims 1 to 8.
10. A double-layer supercapacitor, characterized in that: It comprises a negative electrode shell, an activated carbon electrode, a PP separator, a positive electrode shell and an electrolyte; the activated carbon electrode is made of the nitrogen self-doped activated carbon according to claim 8.
Citation Information
Patent Citations
Method for preparing graphene-like carbon nanosheet material through one-step method and application
CN108630453A
Molten salt coating chemical activation method for preparing activated carbon with high specific surface area
CN113860304A
Preparation method of porous carbon film based on Schiff base polymer
CN113914015A
Activated porous carbonaceous material
JP1994032678A
Mesoporous cerium oxide nano-material and preparation method and application thereof
US20250100896A1